Detection of Subtilisin (1-7) Genes and their Relationship to Antifungal Resistance in Several Dermatophyte Isolates - Hendi, Aseel Hasan; Al-Araji, Alaa Mohsin (Iraqi Journal of Science, 2026)
Dermatophytes secrete enzymes that allow them to invade keratin tissues, act as antigens, and trigger inflammatory responses. Subtilisin-like proteins degrade keratin structures, facilitating their infection of body tissues and the host. This study aimed to detect subtilisin genes (SUB1-7) through conventional PCR analysis and to investigate their relationship with the antifungal resistance of certain dermatophyte isolates. Twenty-two isolates obtained from Iraqi patients were identified both morphologically and molecularly, specifically using the internal transcribed spacer (ITS) region. A genomic DNA extraction kit was used to extract genomic DNA from fungal growth. The identified isolates were found to consist of the following species: Trichophyton indotineae, Trichophyton mentagrophytes, Trichophyton rubrum, Trichophyton simii, and Microsporum canis. Six antifungal agents were tested on the dermatophyte isolates using the disk diffusion method. All isolates from every species were found to be susceptible to voriconazole and fluconazole, while most isolates demonstrated resistance to nystatin. Virulence genes SUB2 and SUB5 were not detected in any of the dermatophyte isolates. SUB1 and SUB4 were the most frequently observed genes, while SUB3 was the least frequent. This study is the first in Iraq to reveal subtilisin-like genes and their association with antifungal resistance, especially in T. indotineae.